STRATEGI PENGEMBANGAN AGROINDUSTRI TAHU DI KELURAHAN SADABUAN KECAMATAN PADANGSIDIMPUAN UTARA KOTA PADANGSIDIMPUAN - Ardiansyah, Romi; Martina, Martina; Kembaren, Emmia Tambarta; Yuristia, Rahmi (LPPM Universitas Malikussaleh - Indonesia, 2022)
This research was carried out in the Tofu Agroindustry of Bapak Hakim Sadabuan Ward, North Padangsidimpuan District, Regency Padangsidimpuan in August 2022. Although Bapak Hakim Tofu Agroindustry has been running for a long time but various obstacles and problems faced by this agro-industry are. the non-fulfillment of soybeans in the Padangsidimpuan area so that they had to buy raw materials from outside because Mr. Hakim bought the soybeans directly from a warehouse in Medan City so that there were additional costs in the soybean delivery process. Then there are several tofu household businesses in North Padangsidimpuan District so it is very possible that there is very fierce competition among tofu entrepreneurs, the lack of labor. This study aims to formulate a development strategy that can be applied by Bapak Hakim Tofu Agroindustry in Sadabuan Ward North Padangsidimpuan District Padangsidimpuan Legency. The data analysis method uses descriptive qualitative and SWOT analysis. The type of data in this study is qualitative data. The data sources in this study are primary data and secondary data. The results of this study show that Bapak Hakim Tofu Agroindustry has internal strength but on the other hand faces various threats from external agro-industry with a value of 0. 80 or X > 0 and -0.20 or Y < 0. Agro-industrial development strategy Bapak Hakim Tofu Agroindusrty is in quadrant II, in this position the focus of the development strategy applied is the S-T strategy (Strenght-Threats) which is to utilize the strengths possessed to deal with various threat